Antimicrobial Stewardship Programs: A Review of Strategies to Avoid Polymyxins and Carbapenems Misuse in Low Middle-Income Countries - Fabrício Rodrigues Torres de Carvalho; João Paulo Telles; Felipe Francisco Bodan Tuon; Roberto Rabello Filho; Pedro Caruso; Thiago Domingos Correa (MDPI AG, 2022)
Antibiotics misuse and overuse are concerning issues worldwide, especially in low middle-income countries. These practices contribute to the increasing rates of antimicrobial resistance. One efficient strategy to avoid them is antimicrobial stewardship programs. In this review, we focus on the possible approaches to spare the prescription of polymyxins and carbapenems for the treatment of Acinetobacter baumannii, carbapenem-resistant Enterobacterales, and Pseudomonas aeruginosas infections. Additionally, we highlight how to implement cumulative antibiograms and biomarkers to a sooner de-escalation of antibiotics.